2016
DOI: 10.1016/j.pec.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Sharing news of a lung cancer diagnosis with adult family members and friends: a qualitative study to inform a supportive intervention

Abstract: Objective Extensive research exists on breaking bad news by clinicians. This study examines perspectives of patients and those accompanying them at diagnosis-giving of subsequently sharing news of lung cancer with adult family/friends, and views of healthcare professionals, to inform development of a supportive intervention. MethodsQualitative interviews with 20 patients, 17 accompanying persons; focus groups and interviews with 27 healthcare professionals from four Thoracic Oncology Units. Intervention develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In regards to attitudes and beliefs, an interesting finding is one third of respondents reported that they were unsure if they would inform their family of findings of high risk of a disease with their family. This result is consistent with literature that report individuals find disclosing their diagnosis as challenging (Ewing et al 2016) and express worry and concern about the reaction (Hilton et al 2009). Another interesting finding was that many (~40%) participants reported they were unsure if knowing they were at high risk of developing any deadly disease would influence their decision to have children.…”
Section: Discussionsupporting
confidence: 92%
“…In regards to attitudes and beliefs, an interesting finding is one third of respondents reported that they were unsure if they would inform their family of findings of high risk of a disease with their family. This result is consistent with literature that report individuals find disclosing their diagnosis as challenging (Ewing et al 2016) and express worry and concern about the reaction (Hilton et al 2009). Another interesting finding was that many (~40%) participants reported they were unsure if knowing they were at high risk of developing any deadly disease would influence their decision to have children.…”
Section: Discussionsupporting
confidence: 92%
“…Signposting patients to appropriate services after an initial assessment was particularly helpful when the nurse specialist was faced with the more sensitive, demanding and challenging needs of patients, such as patients' need for help to explain cancer to their children. Bringing up cancer diagnosis with the family (especially at school or under school age children) is a well-known concern and potentially distressful act for patients regardless of type of cancer (Asbury et al, 2014;Ewing et al, 2016), and one that professionals in the medical and nursing sciences may struggle to help with (Banerjee et al, 2016). Expert support provided by the afore-mentioned services (in the form of one-to-one counselling or peer support, or via group therapy) is indispensable at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers take a variety of roles in assisting patients' journeys in health management. Like Connie, caregivers are often tasked with sharing news of a diagnosis with the patient and others-A multifaceted role that involves deciding (1) what information should be shared, (2) when to share it, and (3) how the news should be shared [45]. Caregivers are in need of communication skill building, as their interactions are a key factor in enacting support and decisions for good patient outcomes [46,47].…”
Section: Caregiversmentioning
confidence: 99%